Knockdown of Ube2w increases the susceptibility to dextran sodium sulfate-induced ulcerative colitis in mice - WANG Shao-xin, CUI Li-hong, LI Xiao-wei, LIU Xin-yao, LUO Zhe, YAN Zhi-hui (Jichu yixue yu linchuang, 2021)
Objective To investigate the effect of UBE2W on dextran sodium sulfate (DSS)-induced ulcerative colitis in mice. Methods Different interference sequences of UBE2W siRNA(1#, 2# and 3#) were transiently transfected into mouse fibroblast cell line L929.The expression of UBE2W protein was detected by Western blot. The siRNA with the most significant inhibitory effect was selected for transfection in vivo. Ten C57BL / 6 male mice were randomly injected with siRNA (siUbe2w/si-control) via caudal vein and fed with 2.5% DSS to construct two groups of DSS ulcerative colitis models, Ube2w knockdown group and control group with 5 mice in each group. Western blot and RT-qPCR were used to detect the expression of UBE2W in colon tissue of mice. The weights of mice in the two groups were observed, and the severity of colitis was compared by histological score. Results Ube2w siRNA 2# inhibited UBE2W protein expression most significantly in L929 cells. UBE2W mRNA and protein expression in colon tissue of Ube2w knockdown group were lower than those in control group, and weight loss in Ube2w knockdown group was significantly more obvious than that in control group, and the histological score of colitis in knockdown group was 8.60±0.24, which was higher than that in control group (5.20±0.49)(P＜0.05). Conclusions UBE2W is involved in the regulation of inflammatory response and Ube2w knockdown increases the susceptibility to DSS induced ulcerative colitis in mice.